Superovulation in mares: Limitations and perspectives - Alvarenga, Marco Antonio [UNESP]; Carmo, Marcio T. [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Hippiatrika Verlag Mbh, 2008)
Superovulation is an important tool for routine use in equine embryo transfer (ET) in order to reduce the costs and to enhance the efficiency of ET programs. Satisfactory superovulatory answers (2-7 ovulations) have been reported in mares treated with Equine Pituitary Extract (EPE) and more recently using a commercial Equine FSH. However, embryo recovery rates have been inconsistent and below expectations (20-50% embryos/ovulation). Recent studies have shown that superovulatory treatment leads to disturbances in oocyte maturation and transport, especially in mares with a high ovarian response. Higher and more consistent embryo recovery rates per ovulation have been observed in mares treated with lower doses of EPE. This paper presents a review of recent studies related to superovulation in mares.
Keywords: superovulation; horse; oocyte maturation; embryo transfer; equine pituitary extract; equine FSH; reproduction